A New Adjustable Puncture Device for In Situ Fenestration During Thoracic Endovascular Aortic Repair. (August 2018) - Wang, Lixin; Zhou, Xiushi; Guo, Daqiao; Hou, Kai; Shi, Zhenyu; Tang, Xiao; Fu, Weiguo
Purpose: To describe a new adjustable puncture system for in situ fenestration in thoracic endovascular aortic repair (TEVAR).Technique: An adjustable puncture needle for use in conjunction with a steerable 8-F, 55-cm Fustar sheath is demonstrated in a 65-year-old man with acute complicated type B dissection involving the left subclavian artery (LSA). The puncture device features an inflatable balloon at the tip, a central lumen for 0.018-inch guidewires, and a 3-level puncture depth. After thoracic stent-graft deployment at zone 2, the needle/sheath combination was delivered from a left brachial artery access. The needle was adjusted perpendicular to the fabric of the stent-graft with the assistance of the steerable sheath. The balloon at the tip was inflated to center the needle, and the puncture depth was selected on the puncture needle system. Holding the sheath and puncture needle together, a hole was created in the graft fabric. The aperture was sequentially dilated to accommodate the mating stent selected to maintain perfusion to the LSA. This new device has been successfully applied in 6 patients treated with TEVAR for different arch pathologies.Conclusion: This new puncture device could assist in situ fenestration and improve the technical success rate.